Reevaluation of the cranial osteology and phylogenetic position of the early crocodyliform Eopneumatosuchus colberti, with an emphasis on its endocranial anatomy. Issue 10 (22nd October 2021) - Melstrom, Keegan M.; Turner, Alan H.; Irmis, Randall B.
Abstract: Eopneumatosuchus colberti Crompton and Smith, 1980, known from a single partial skull, is an enigmatic crocodylomorph from the Lower Jurassic Kayenta Formation. In spite of its unique morphology, an exceptionally pneumatic braincase, and presence during a critical time period of crocodylomorph evolution, relatively little is known about this taxon. Here, we redescribe the external cranial morphology of E . colberti, present novel information on its endocranial anatomy, evaluate its phylogenetic position among early crocodylomorphs, and seek to better characterize its ecology. Our examination clarifies key aspects of cranial suture paths and braincase anatomy. Comparisons with related taxa (e.g., Protosuchus haughtoni ) demonstrate that extreme pneumaticity of the braincase may be more widespread in protosuchids than previously appreciated. Computed tomography scans reveal an endocranial morphology that resembles that of other early crocodylomorphs, in particular the noncrocodyliform crocodylomorph Almadasuchus figarii . There are, however, key differences in olfactory bulb and cerebral hemisphere morphology, which demonstrate the endocranium of crocodylomorphs is not as conserved as previously hypothesized. Our phylogenetic analysis recovers E . colberti as a close relative of Protosuchus richardsoni and Edentosuchus tienshanensis, contrasting with previous hypotheses of a sister group relationship with Thalattosuchia. Previous work suggested the inner ear has some similarities to semi‐aquatic crocodyliforms, but the phylogenetic placement of E . colberti among protosuchids with a terrestrial postcranial skeletal morphology complicates paleoecological interpretation.